Pembagian Harta Warisan Berdasarkan Hukum Adat - Tuharea, Fatma Wati; Angga, La Ode; Lakburlawal, Mahrita Aprilya (BAMETI Customary Law Review, 2024)
Customary inheritance law is the legal rules that regulate how to pass on and transfer tangible and intangible assets from generation to generation. Thus, customary inheritance law contains three elements, namely the existence of inheritance or inherited assets, the existence of heirs and heirs. Apart from the three elements of customary inheritance law, it is also influenced by the three kinship systems that exist in Indonesian society, namely the patrilineal system, matrilineal system, and parental or bilateral system so that customary law in Indonesian society is a diverse law. Indonesian society still applies the distribution of inheritance according to customary law, one of which is in Maluku Province, namely Elfule Village which adheres to a patrilineal kinship system, namely the lineage that originates from the father. This can be seen from the clan of the residents of Elfule Village. With this background, the status of men in among indigenous peoples is automatically higher than women. If property is distributed according to customary law in Elfule Village, it is important to note that the son who receives the inheritance from his parents' inheritance is the oldest son. The method used in this research is the sociological juridical method. Research data sources include primary data sources and secondary data sources. Data collection was obtained through interviews and then the data was processed and analyzed qualitatively. The results of the research show that Elfule Village in principle adheres to a patrilineal kinship system, namely the line of descent from the father so that in the distribution of inheritance, Elfule Village adheres to a male majoritarian system, however, in developments based on research results, it turns out that the inheritance process in Elfule Village has experienced a shift where some of the female children have get an inheritance from the assets inherited from their parents such as villages and long-lived plants, why is the daughter's share smaller because when the daughter marries she will follow her husband and join his new family, in this case the distribution of inheritance is done before the heir dies.